(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The number of Internet of Things (IoT) applications is rapidly increasing. Current cloud-centric IoT designs, on the other hand, are unable to meet the mobility and dormancy necessities of duration precarious IoT practices. In certain industries, the practices have hampered the expansion of IoT. The computation in the Fog model is investigated in the present study as an option for IoT applications. Fog computing problems or obstacles for IoT applications must be thoroughly reviewed and synthesized. This study uses a well-known and commonly used method of systematic literature review (SLR) technique to address this critical research requirement. From an initial collection of 439 publications, 17 relevant studies were selected and examined by means of the SLR method and specific searching conditions generated from the study topic. In addition, four papers were hand-selected based on the significance to the topic. The collected information from the review was divided into a set of primary difficulty groups. The verdicts of the presented study may assist practitioners and scholars in better understanding fog computing problems, as well as providing a variety of valuable acumens for upcoming research. Range or scope of the study mainly is restricted to collection of the resources that have been evaluated from the database.